Liver function tests as a prognostic indicator in Pediatric Intensive Care Unit (PICU) - Mallikarjuna, Akshatha; Sood, Ashwani K. S (International Journal of Contemporary Pediatrics, 2018)
Background: Frank liver failure is incompatible with life. Severity of liver disease is reflected in clinical signs or biochemical alterations. Hepatic dysfunction indicates poor outcome in critically ill patients, but no large systematic investigation into its exact incidence and prognostic relevance has been performed in different population groups. Methods: All PICU admissions during the study period were included. Pattern of admission LFT (Liver Function Tests) was reported. Relationship between clinical events and patient outcome with the LFT panel on day 1 and day 3 were reported. Association between final outcome and day 7 LFT was explored. Results: Deranged AST (Aspartate Transaminase), ALT (Alanine Transaminase), Bilirubin, Albumin, PT (Prothrombin time) and INR (International Normalized Ratio) on Day1 and 3 had significant association with increased requirement of inotropic and ventilatory support as well with increased mortality. LFT parameters on day 7 showed significant correlation between normal AST, ALT, bilirubin, PT and INR with improved survival. Conclusions: LFT’s should be essential part of biochemical profile and doctors caring for sick patients in peripheral hospitals should consider for early referral of patients to higher centers based on LFT parameters for the advanced care they deserve.